2019
DOI: 10.1186/s12889-019-6895-x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational readiness for wellness promotion – a survey of 100 African American church leaders in South Los Angeles

Abstract: Background Churches are an important asset and a trusted resource in the African American community. We needed a better understanding of their readiness to engage in health promotion before launching a large-scale health promotion effort in partnership with South Los Angeles churches. Methods In 2017, we conducted surveys with leaders of 100 churches. Surveys were conducted face-to-face (32%) or by telephone (68%) with senior pastors (one per church) and lasted on avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Congregational resources such as the number of participants and staff as well as providing health-focused education programs and having a nonprofit were positively associated with offering substance programming, consistent with prior research showing a connection between congregational resources and the provision of health-related programs (Fulton, 2011; Haughton et al, 2020; Trinitapoli et al, 2009; Wong et al, 2017). Larger congregations and more paid staff have been associated with having congregational health or wellness programs and community outreach programs (Hatchett et al, 2011; Maxwell et al, 2019; Tagai et al, 2018). Congregations without such resources may need to establish partnerships with outside health organizations that can provide the resources to support the implementation of health programs (Harper et al, 2014; Haughton et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congregational resources such as the number of participants and staff as well as providing health-focused education programs and having a nonprofit were positively associated with offering substance programming, consistent with prior research showing a connection between congregational resources and the provision of health-related programs (Fulton, 2011; Haughton et al, 2020; Trinitapoli et al, 2009; Wong et al, 2017). Larger congregations and more paid staff have been associated with having congregational health or wellness programs and community outreach programs (Hatchett et al, 2011; Maxwell et al, 2019; Tagai et al, 2018). Congregations without such resources may need to establish partnerships with outside health organizations that can provide the resources to support the implementation of health programs (Harper et al, 2014; Haughton et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, as noted above, congregational substance use programs likely supplement rather than replace government-funded services, similar to a previous in-depth exploration of congregational health programs that suggested most tend to be episodic, small in scale, and local in scope, although congregations are distinctive in being able to identify unmet local needs and network in productive ways (Werber et al, 2014). Therefore, partnerships among congregations, substance use professionals and academic institutions, or public health researchers are likely needed to address unmet substance use needs (Maxwell et al, 2019). Federal initiatives such as the Faith-based and Community Initiatives, particularly as implemented by SAMHSA, are important for promoting such partnerships, as they provide faith-based partners with block and formula grant funding and training programs and curricula (SAMHSA, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We found that one-third of FBOs already had these relationships, which can be leveraged for health programming. A recent study among African American churches found that 65% had existing collaborations with health clinics or other organizations [34]. This suggests that churches may be adept at forming these relationships, although there may be room to further expand upon faith-based collaborations with health organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies have investigated church characteristics that predict their readiness and capacity for HPP (Maxwell et al, 2019). Initial findings reveal that larger congregations, funding for HPP, paid staff, and health ministries are associated with HPP delivery (Maxwell et al, 2019).…”
Section: > > Assessment Of Needsmentioning
confidence: 99%
“…African Americans (AAs) remain largely underrepresented in clinical trials, perpetuating health disparities (Julian McFarlane et al, 2021). AA churches are trusted organizations within the AA community, and their successful collaborations with academic institutions to conduct health promotion programming (HPP) and increase AA representation in clinical trials are well documented (Julian McFarlane et al, 2021; Maxwell et al, 2019). Fewer studies have investigated church characteristics that predict their readiness and capacity for HPP (Maxwell et al, 2019).…”
Section: Assessment Of Needsmentioning
confidence: 99%